Sociopolitical effects of new biotechnologies in developing countries - Leisinger, Klaus M. (International Food Policy Research Institute, 1996)
Assuring food security for the next 25 years requires meeting a number of political, social, economic, and technical challenges. One of these is the successful use of new biotechnologies in agriculture. Research in recombinant genetics and biotechnology aims to develop plant varieties that provide reliable high yields at the same or lower costs by breeding in qualities such as resistance to disease, pests, and stress factors such as aridity. Realization of these goals could lead to tremendous gains in food production. However, biotechnology is now evoking the same objections that have been raised against the Green Revolution--that its benefits are distributed inequitably in favor of the large, rich farmers and that it is potentially environmentally destructive. In this brief, Leisinger discusses the need for biotechnology and its sociopolitical ramifications and he looks at the roles played by the public and private sectors. In conclusion, the author states that biotechnology offers no silver bullet for food security -- there are no silver bullets--but biotechnology is an important instrument in the difficult fight against hunger. The sociopolitical obstacles must be removed not only for the successful implementation of biotechnology, but also for an equitable and sustainable tomorrow for the world.